Forma colaborante para elementos estruturais usuais de concreto armado - produzida com matriz cimentícia, reforçada com armadura têxtil, de tecido de juta, impregnada com resina de epóxi - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This work refers to the development of a cooperative cementitious form, with the purpose of replacing traditional wooden forms used in construction sites, for the production of concrete structural elements, like beams, slabs and pillars. It is ribbed panels of thin thickness, molded composite, consisting of a solid phase of cementitious matrix with the combined features of self-compacting concrete mortars (SCC) and the of high-strength concrete mortars (HSC). The other dispersed phase, which corresponds to, is a textile armor, which uses a jute fiber fabric impregnated with epoxy resin. In this work, the methodology applied was the exploratory and experimental, and the results analyzed quantitatively. The components of the cementitious matrix and of textile armor, were characterized physically and chemically, according to ABNT and through mass spectrometry x-ray fluorescence (FRX), by x-ray diffraction (DRX) and x-ray Laser. In the development of textile armor, procedures were carried out for the jute fabric coating with epoxy resin impregnation. Likewise, in the development of cementitious matrix, experimental procedures were carried out, in the sense of getting the dosage in desirable proportions of a trace, which awarded her features of great fluidity, self-leveling and high resistance, properties of a concrete of high performance concrete (HPC). Samples of the cementitious matrix and of textile armor, were analyzed individually through bodies of evidence, for verification of their acquired properties. After the optimization of composite developed, were produced form cooperative boards measuring 40 x 40 cm, which served as a bodies of evidence during the tests and analyses of the mechanical behavior. In addition to these essays the plates were evaluated the durability as regards absorption and impermeability, was also checked, the compactness and completeness of the internal aspects of the microstructure of composite, using optical microscopy. The results obtained, entrusted to the cementitious matrix, characteristics of high performance concrete (HPC II) with characteristic resistance in axial compression of fck 118.9 MPa and to the textile reinforcement, the ability to resist the maximum direct traction voltage of 70.8 MPa. The cementitious cement plate of the collaborative form produced with the composite, reached the maximum resistance of 17.0 MPa of flexural traction.
Collaborative form for the usual structural elements of reinforced concrete - produced with cementitious matrix, reinforced with textile armor of jute fabric, impregnated with epoxy resin.
Keywords: Concreto; Concreto armado; Juta; ENGENHARIAS; Forma colaborante; Armadura têxtil; Concreto CAA; Concreto CAR; Concreto CAD